Estratégias adaptativas da linhagem não ambiental Escherichia coli DH5-α ao herbicida mesotrione - Olchanheski, Luiz Ricardo (2014)
The intensive use of agrochemicals has assumed an important role in increasing agricultural production; however, one of the impacts has been changes in population structure of microbiota in the soil, which need to tolerate the xenobiotics that are applied in order to survive. A pertinent question is whether these mechanisms are selected by the presence of different agrochemicals in soils, or if there are constitutive mechanisms of adaptation. The aim of this study was to evaluate the defense system of an un-environmental strain, E. coli DH5-α, in relation to the herbicide mesotrione, which had no prior contact with the soil. The results showed that this strain was able to tolerate higher doses of the herbicide, and that the determination of the herbicide by a method developed and validated by high performance liquid chromatography (HPLC), made it possible to determine the complete disappearance of mesotrione in the sample after 3 h of exposure. Growth rates in the treatment with the herbicide were lower than the control, prior to the period of degradation, showing the toxic effect on the bacterial cells. As regards defense systems, it was noted that changes in the saturation of the membrane lipids reduced the damage caused by reactive oxygen species and possibly hindered the entry of xenobiotics in the cell, as well as activating GST enzyme activity in the antioxidant system and in the metabolizing process of the herbicide. Considering that E. coli DH5-α showed no previous contact with mesotrione, the defense system found in this strain can be considered as general and non-specific. This strategy may be interesting in the adaptation of bacterial strains in agricultural soils, which are subject to changing herbicides in an ever more intense manner.